Research Active Programme: an inclusive research module in 3rd level education. (7th August 2013) - Salmon, Nancy; Carey, Eileen
Abstract : Accessible summary: The Research Active Programme (RAP) was a set of eight sessions offered at the University of Limerick enabling self‐advocates to learn how to do research on their own or with others. This short paper describes this programme and celebrates the great work RAP graduates are doing now. A link to a poster designed by six self‐advocates about RAP is included.